Phonon-Polaritons in Lead Halide Perovskite Film Hybridized with THz Metamaterials - Kim, Hwan Sik; Ha, Na Young; Park, Ji Yong; Lee, Soonil; Kim, Dai Sik; Ahn, Yeong Hwan (Nano Letters, 2020)
In this work, we demonstrated a phonon-polariton in the terahertz (THz) frequency range, generated in a crystallized lead halide perovskite film coated on metamaterials. When the metamaterial resonance was in tune with the phonon resonance of the perovskite film, Rabi splitting occurred due to the strong coupling between the resonances. The Rabi splitting energy was about 1.1 meV, which is larger than the metamaterial and phonon resonance line widths; the interaction potential estimation confirmed that the strong coupling regime was reached successfully. We were able to tune the polaritonic branches by varying the metamaterial resonance, thereby obtaining the dispersion curve with a clear anticrossing behavior. Additionally, we performed in situ THz spectroscopy as we annealed the perovskite film and studied the Rabi splitting as a function of the films' crystallization coverage. The Rabi splitting versus crystallization volume fraction exhibited a unique power-law scaling, depending on the crystal growth dimensions.
Keywords: Anticrossing behavior; Crystallization volume; Dispersion curves; Halide perovskites; Interaction potentials; Power law scalings; Strong-coupling regime; Terahertz frequencies; Crystal domain; Metamaterials; Perovskite; Phonon-polariton; Strong coupling; Terahertz